Effect of Knowledge/Practice of COVID-19 Prevention Measures on Return-to-Work Concerns; Attitudes About the Efficacy of Traditional Chinese Medicine: Survey on Supermarket Staff in Huanggang, China - Li, Lingru; Meng, Yue; Wang, Ji; Zhang, Ying; Zeng, Yong; Xiao, Huiqun; He, Jiangming; Liu, Zhenquan; Hou, Shujuan; Li, Tianxing; Qin, Jingbo; Fang, Yini; et al. (Frontiers in Public Health, 2021)
Objective: The objective of this study was to investigate how knowledge and practice of coronavirus disease 2019 (COVID-19) prevention measures affected concerns about returning to work among supermarket staff. Attitudes about the ability of traditional Chinese medicine (TCM) to prevent COVID-19 were also assessed. Methods: A cross-sectional study was conducted in Huanggang, Hubei Province, China from April 23 to 25, 2020. Participants were invited to fill out an electronic questionnaire on their cell phones. Results: The results showed that from 2,309 valid questionnaires, 61.5% of participants were concerned about resuming work. Major concerns included asymptomatic infection (85.01%) and employees gathering in the workplace (78.96%). Multivariate logistic regression indicated that the female gender, having school-aged children and pregnancy were risk factors for being concerned about resuming work, while good knowledge and practice of preventive measures were protective factors. Knowledge and practice of preventive measures were positively correlated. Among preventive measures, the highest percentage of participants knew about wearing masks and washing hands. Meanwhile, 65.8% of participants expressed confidence in the ability of TCM to prevent COVID-19, where 74 and 51.3% thought there was a need and a strong need, respectively, for preventive TCM-based products. Among them, 71.5% preferred oral granules. Regarding TCM as a COVID-19 preventative, most were interested in information about safety and efficacy. Conclusion: These findings suggested that promoting knowledge and practices regarding COVID-19 prevention can help alleviate concerns about returning to work. Meanwhile, TCM can feasibly be accepted to diversify COVID-19 prevention methods. Clinical Trial Registration:http://www.chictr.org.cn/, identifier: ChiCTR2000031955.